EFFECT OF ANCYLOSTOMIASIS ON LIVER PROTEIN, AMINO ACIDS AND GST (GLUTATHIONE - S - TRANSFERASE) LEVEL IN MALE SWISS ALBINO MICE - GOLLAPUDI, VINOD KUMAR; VARDHANI, V. VIVEKA (The Bioscan, 2013)
The level of total protein, amino acids and GST (Glutathione –S- transferase) was estimated in the liver of male Swiss albino mice infected with various single doses (group A, 500 dose; group B, 1000 dose and group C, 2000 dose) of infective larvae of Ancylostoma caninumon day 1, 4, 9, 16 and 30 after infection. The level of liver protein was significantly increased in all the three groups (A, B and C) of mice when compared with control groups (a, b and c) on day 1, 4, 9, 16 and 30 of infection with a peak response on day 16 of infection (in all the three groups); in groups A, B and C, there was a sudden decline of liver protein on day 30 (still higher than control). Significant increase of amino acids and GST was found from day 1 to 30 in all the 3 groups of mice. The highest level of amino acids and GST was recorded on day 16 in mice of groups A and C and on day 9 in mice of group B. Increase of liver protein, amino acids and GST in infected mice indicates the occurrence of oxidative stress in hepatocytes due to infection which might be causing abnormality in energy metabolism.